Advances in Computer Science - ASIAN 2006. Secure Software and Related Issues - Mitsu, Okada (Springer, 2017)
The series of annual Asian Computing Science Conferences (ASIAN) was initi- ated in 1995 by AIT, INRIA and UNU/IIST to provide a forum for researchers in computer science from the Asian region and to promote interaction with re-searchers from other regions. The first ten conferences were held, respectively, in Bangkok, Singapore, Katmandu, Manila, Phuket, Penang, Hanoi, Mumbai, Chi-ang Mai, and Kunming. The 11th ASIAN conference was held in Tokyo, Japan, December 6-8, 2006. Each year, the conference focuses on a different theme at the cutting edge of computer science research. The theme of ASIAN 2006 wassecure software. Three distinguished speakers were invited to the conference